FEATURES OF THE THORACIC CAGE HISTOLOGICAL ORGANIZATION IN WHITE LABORATORY RATS - Dihtiar, V.A.; Kaminska, M.O. (World of Medicine and Biology, 2019)
A histological examination of the thoracic cage was carried out on 3 months aged white laboratory rats. It has been established that the ribs attached to the sternum do not have a head and neck, the body is made of hypertrophied cartilage covered with perichondrium. A clear boundary in the areas of the ribs fastening to the sternum was not found. The rib is adherent to the synchondrosis with hyaline cartilage. Growth zones are located between the synchondrosis and the sternum segments. In the areas of the ribs attachment to the vertebral body in rats a joint is formed, the head of the rib is covered with articular cartilage without a clear division into zones. On the side of the vertebral body, the articular fossa is made of fibrous cartilage. In terms of the pathological conditions modeling, the data obtained can be considered as control.